DESAIN ANTENA MIKROSTRIP E-SHAPED PATCH PADA FREKUENSI 5500 MHz UNTUK WIFI - Fitri Elvira Ananda; Shita Fitria Nurjihan; Muhammad Arif Rahman (Universitas Halu Oleo, 2021)
Modifying the shape of the patch microstrip antenna is one way to solve the narrow bandwidth. E-Shaped patch microstrip antenna is obtained by modifying a rectangular patch mikrostrip antenna. The results on this research have succesfully compared the design and simulation antenna parameters between rectangular patch and E-shaped patch. It uses FR-4 as a substrate and works on 5500 MHz frequency for WiFi. The feeding method using a feedline method. The E-shaped patch microstrip antenna has a VSWR value of 1.04 and the antenna return loss is -33.73 dB, better than the rectangular patch. The gain of E-shaped patch is increased by almost 2.5 times and the bandwidth is increased by 10.18% compared to the rectangular patch. The radiation pattern of the two patches has the same directional radiation pattern.